Renewable Waste-to-Energy in Southeast Asia: Status, Challenges, Opportunities, and Selection of Waste-to-Energy Technologies - Maw Maw Tun (Applied Sciences, 2020)
Rapid urban population growth that boosts increased waste generation and electricity demand has led to a possible alternative waste-to-energy solution in Southeast Asia. Despite some issues related to the development of the waste-to-energy sector such as public perception, all stakeholder involvement, public–private partnerships, funding, and climate factors, some Southeast Asian countries have made a reasonably successful step toward the developed technologies. Therefore, this study aimed to highlight an overview of the waste-to-energy sector in Southeast Asian countries to specify the status, challenges, opportunities, and selection of the technologies suited for the specific country. In order to achieve this aim, the study collected, synthesized, and evaluated data about waste resources, current waste management, waste-to-energy utilization, and its potential in the region based on published research papers and policy reports. It was found that the major waste-to-energy technologies in the region are incineration, landfills with gas capture, and anaerobic digestion. The total quantity of the waste-to-energy capacity from landfill biogas plants, incineration plants, and other waste-to-energy practices in the region accounts for over 323 MW at present and is expected to grow to double its current size by 2022. Meanwhile, by 2030, the realizable generation potential from renewable municipal waste in six Southeast Asian countries (Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam) amounts to 17.26 terawatt-hours (TWh). The study also specifies the requirements and considerations for the selection of waste-to-energy technologies, as well as the dimensions related to the development of the technologies. Additionally, four major aspects—technical, financial, environmental, and social and political—regarding the challenges and opportunities for the development of these technologies are considered. The challenges and opportunities related to the development of waste-to-energy in the region reveal how to overcome the drawbacks and to grasp the benefits at present and in the near future. Finally, the study is concluded with suggestions for the selection of the technologies in the region.